2021
DOI: 10.1063/5.0060139
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement density and particle dynamics in rigid interfacial layers of polymer nanocomposites

Abstract: Intermixing between chemically different polymers around nanoparticles creates chemically heterogeneous layers, exhibiting unusual dynamic anomalies due to dynamic confinement and coupling phenomena in polymer nanocomposites. Interfacial mixing of chains is possible when adsorbed chains are mobile above their glass-transition temperature, leading to enhanced entanglement density at the interphase. Linear rheology data of polymer nanocomposites with chemically heterogeneous interphases around nanoparticles were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…In previous studies, we studied the role of chain rigidity on the reinforcement of PEO and poly(methyl acrylate) (PMA) nanocomposites. 20,27,39 We showed that particles adsorbed with less rigid polymers improved the entanglement density of PMA matrix chains. 20 Consequently, the dense interphase layer slowed down the matrix polymer dynamics and the particle diffusion.…”
Section: ■ Introductionmentioning
confidence: 90%
See 4 more Smart Citations
“…In previous studies, we studied the role of chain rigidity on the reinforcement of PEO and poly(methyl acrylate) (PMA) nanocomposites. 20,27,39 We showed that particles adsorbed with less rigid polymers improved the entanglement density of PMA matrix chains. 20 Consequently, the dense interphase layer slowed down the matrix polymer dynamics and the particle diffusion.…”
Section: ■ Introductionmentioning
confidence: 90%
“…Interfacial chain mobility gradient, chain relaxations, and particle dynamics have been extensively explored to understand the dynamic response of polymer nanocomposites. 9−17 The viscoelastic properties of composites consisting of one homopolymer type are governed by chain conformations, 18,19 adsorption, 18,20,21 and confinement of chains 22−25 in the vicinity of nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations